2020
DOI: 10.1111/sji.12886
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XLOC_003810 promotes T cell activation and inhibits PD‐1/PD‐L1 expression in patients with myasthenia gravis‐related thymoma

Abstract: This study aimed to investigate the effect of long non‐coding RNA XLOC_003810 on the activation of CD4+ T cells and expression of PD‐1/PD‐L1 in patients with myasthenia gravis‐related thymoma (MG‐T). Thymus specimens and thymic mononuclear cells were obtained from MG and MG‐T patients or cardiac surgery patients undergoing thoracotomy who were selected as negative controls (NC). XLOC_003810 expression was examined using quantitative real‐time PCR (qRT‐PCR). Frequency of CD4+ T cells and proportion of CD4+PD‐1+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…MG is a complex disease and the pathogenetic mechanisms and autoimmune processes involved are still unclear. An extensive body of evidence now supports the fact that lncRNAs play a regulatory role in the immune system and can exert influence in numerous autoimmune diseases and MG 7 , 36 . The identification of SNPs in lncRNA-mediated ceRNA regulation pairs in MG by considering relevant risk pathways could help us to illustrate the potential roles of lncRNA-SNPs in the progression of MG.…”
Section: Discussionmentioning
confidence: 97%
“…MG is a complex disease and the pathogenetic mechanisms and autoimmune processes involved are still unclear. An extensive body of evidence now supports the fact that lncRNAs play a regulatory role in the immune system and can exert influence in numerous autoimmune diseases and MG 7 , 36 . The identification of SNPs in lncRNA-mediated ceRNA regulation pairs in MG by considering relevant risk pathways could help us to illustrate the potential roles of lncRNA-SNPs in the progression of MG.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple lncRNAs have been shown to be involved in the process. For instance, Bo Hu et al revealed that lncRNA XLOC_003810 decreased the proportion of CD4 + PD-1 + T cells in patients with MG [33].…”
Section: Activationmentioning
confidence: 99%
“…XLOC_003810 silencing has resulted in opposite effects. Cumulatively, XLOC_003810 is an lncRNA that enhances T cells activation and suppresses PD-1/PD-L1 signaling in MG-T patients [ 10 ]. Another study has shown higher levels of XLOC_003810 in thymic CD4+ T cells obtained from MG-T patients compared with the control group.…”
Section: Lncrnas and Mgmentioning
confidence: 99%